Phonatory Vocal Tract Stability in Stuttering Children before and after Fluency–Enhancing Therapy - Dehqan, A; ali Dashti, G; Mirzadeh, M (Kathmandu University Medical Journal, 2012)
Background Stuttering is a complex disorder. Essentially, it is a neuromuscular disorder whose core consists of tiny lags and disruptions in the timing of the complicated movements required for speech. Objective The purpose of the current study was to collec and comparg jitters and shimmer values in children who stutter before and aftea fluency – enhancing therapy. Methods Subjects consisted of 15 Iranian preschool girls with stutterg, and 15 Iranial preschool girls without afflictions, matched according to age. Vocal jittering and shimmer measurements of thesphonation of the children were compared before and after therapy. Each subject phonated vowels nine times in a random order. Each phonation was sustained for at least five seconds and was recorded. The middle three-second portion of each recorded vowel phonation was subjected to jitter and shimmer analysis. Results On shimmer measures between pre-treatment and post treatment, significant differences were found in all sustained vowels of persons who stutter group and means of shimmer in post therapy were significantly lowerthan pre-treatment. Differences in jitter measurements were not significant between pre-treatment and post-treatment statuses and this parameter did not change after therapy. Conclusion The findings showed that therapy resulted in decreaseg irregularity in the amplitude of vibrations (shimmer). In other words, the therapy increases the steady-state of the laryngeal system. Moreover, this parameter may be used as an index for the effectiveness of therapy. <!--[if !supportEmptyParas]--> <!--[endif]--> <!--[if !supportEmptyParas]--> <!--[endif]--> http://dx.doi.org/10.3126/kumj.v8i4.6240 Kathmandu Univ Med J 2010;8(4):405-9